A case study on the phenomenon of "Barang" - Ragasa, Grace Quaile (1999)
The phenomenon of "barang" was investigated by the researcher. It is the objective of this study to know the process of "barang", to understand the nature of a "mambabarang/barangan" and its significance to the community. It is also the primary goals of this study to know the ways and means in protecting oneself from "barang". The researcher hypothesized that, "barang" ia a means of living of a "mambabarang/barangan". The participants of this research were Helen (not her real name); Professor Dulce Anacion; Bryan N. (not his real name) and Leda Pallomina, a victim of "barang" and "hilo". The researcher concluded that "barang" is not only a means of living of a "mambabarang/barangan". Barang is their way of fulfilling their role in the society as a mambabarang/barangan. The researcher conducted this study through interview using tape recorder, pen and paper.